The Prevalence of Psychological Symptoms in Pregnant Healthcare Workers (HCWs) and Pregnant Non-HCWs During the Early Stage of COVID-19 Pandemic in Chongqing, China - Liu, Min; Li, Nan; Cai, Xianghao; Feng, Xiaoyan; Wang, Rong; Xiong, Peng (Frontiers in Psychiatry, 2021)
Background: Studies showed that healthcare workers (HCWs) and pregnant women bore the burden of mental problems during the COVID-19 pandemic. While, few studies have focused on the psychological impact of COVID-19 pandemic on pregnant women who work at healthcare settings. This study aimed to investigate and compare the prevalence difference of psychological symptoms between pregnant HCWs and pregnant non-HCWs during the early stage of COVID-19 pandemic in China. Methods: A cross-sectional online survey with anonymous structured questionnaires was conducted from February 15 to March 9, 2020. A total of 205 pregnant women in Chongqing, China was recruited. The mental health status was assessed using symptom checklist-90 (SCL-90). Results: Our sample was comprised with 83 pregnant HCWs (mean age = 29.8) and 122 general pregnant women (mean age = 30.8). The results suggested the prevalence of psychological symptoms (the factor score ≥ 2) among all pregnant women ranged from 6.83% (psychosis symptoms) to 17.56% (obsessive-compulsive symptoms). Compared with pregnant non-HCWs, pregnant HCWs reported higher prevalence of psychological symptoms in ten factors of SCL-90. After controlling the confounding variables, multiple logistic regression demonstrated that pregnant HCWs experienced higher prevalence of psychological symptoms of somatization (18.07% vs. 5.74%, p = 0.012, aOR = 4.09), anxiety disorders (16.87% vs. 6.56%, p = 0.025, aOR = 3.37) and hostility (24.10% vs. 10.66%, p = 0.047, aOR = 2.51) than those among pregnant non-HCW. Conclusion: Our study indicated that pregnant HCWs were more likely to suffer from mental health distress than pregnant non-HCWs during the early stage of COVID-19 pandemic. It is vital to implement targeted psychological interventions for pregnant women, especially for HCWs to cope with distress when facing the emerging infectious diseases.